2020
DOI: 10.1007/s12105-020-01174-8
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Cervical Thyroid Tissue Affected by Fibrosing Hashimoto’s Thyroiditis Mimicking Multifocal Metastatic Papillary Thyroid Carcinoma—A Hard Lesson Learnt from an Unusual Case

Abstract: We describe a case of ectopic cervical thyroid tissue which was involved by fibrosing Hashimoto's thyroiditis and which mimicked metastatic papillary thyroid carcinoma both on fine needle aspiration cytology and biopsy. The patient underwent total thyroidectomy which revealed fibrosing Hashimoto's thyroiditis, but no carcinoma. The entire thyroidectomy specimen was submitted for histopathological assessment. Even in the resected thyroidectomy specimen, there were cytological changes that were strongly reminisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…4 Tan HM, et al reported a 52-year-old female with hypothyroidism and developed an anterior neck (1.0 cm) nodule, which was distinctly separate from the thyroid gland. 5 Aspirate biopsy showed predominance of small lymphocytes, small crowded groups of atypical epithelial cells with large round to ovoid nuclei, and some nuclear grooves; the diagnostic hypotheses were lymph node metastatic carcinoma or lymphocytic thyroiditis. 5 As an excision biopsy was also suspected of metastatic carcinoma, a total thyroidectomy and neck dissection were performed, but fibrosing Hashimoto thyroiditis was confirmed.…”
Section: Dear Editormentioning
confidence: 97%
See 4 more Smart Citations
“…4 Tan HM, et al reported a 52-year-old female with hypothyroidism and developed an anterior neck (1.0 cm) nodule, which was distinctly separate from the thyroid gland. 5 Aspirate biopsy showed predominance of small lymphocytes, small crowded groups of atypical epithelial cells with large round to ovoid nuclei, and some nuclear grooves; the diagnostic hypotheses were lymph node metastatic carcinoma or lymphocytic thyroiditis. 5 As an excision biopsy was also suspected of metastatic carcinoma, a total thyroidectomy and neck dissection were performed, but fibrosing Hashimoto thyroiditis was confirmed.…”
Section: Dear Editormentioning
confidence: 97%
“…5 Aspirate biopsy showed predominance of small lymphocytes, small crowded groups of atypical epithelial cells with large round to ovoid nuclei, and some nuclear grooves; the diagnostic hypotheses were lymph node metastatic carcinoma or lymphocytic thyroiditis. 5 As an excision biopsy was also suspected of metastatic carcinoma, a total thyroidectomy and neck dissection were performed, but fibrosing Hashimoto thyroiditis was confirmed. 5 The authors emphasized the procedures to avoid the misdiagnoses between Hashimoto thyroiditis and thyroid cancer, aiming to prevent the unnecessary surgical interventions.…”
Section: Dear Editormentioning
confidence: 97%
See 3 more Smart Citations